Assessing Emission Allocation in Europe: An Interactive Simulation Approach - Andreas Löschel; Andreas Lange; Tim Hoffmann; Christoph Böhringer; Ulf Moslener (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Implementation of an EU-wide emissions trading system by means of National Allocation Plans is at the core of European environmental policy agenda. Member States are faced with the problem of allocating their national emission budgets under the EU Burden Sharing Agreement between energy-intensive sectors that are eligible for international emissions trading and the remaining segments of their economies that will be subject to complementary domestic emission regulation. The country-specific segmentation of national emission budgets between trading sectors and non-trading sectors will determine the cost efficiency of the EU emissions trading system and the gains for each Member State vis-?-vis domestic abatement policies. We present an interactive simulation model where users can specify the design of National Allocation Plans for each EU Member State and then evaluate the induced economic effects. Our numerical framework is based on marginal abatement cost curves for (emissions) trading and non-trading sectors of the EU-15 economies. Illustrative simulations highlight the importance of a coordinated design of National Allocation Plans in order to avoid substantial excess costs of regulation and drastic burden shifting between nontrading and trading sectors.
Keywords: Q58; D61; H21; H22; 330; emissions trading; allowance allocation; National Allocation Plans; Emissionsrechte; Allokation; Emissionshandel; Simulation; Umweltschutzkosten; Wirtschaftspolitische Wirkungsanalyse; Handelbares Gut; Nicht-handelbares Gut; EU-Staaten